Microbes and oncogenesis - Szkaradkiewicz, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2003)
In recent years the rapid development of genomics permitted to establish the sequences of over 45 microbial genomes. Knowledge of genomic sequences allows to analyse functions of individual genes of a given microorganism and the role played by the gene in the cell. A causal relationship between infection and oncogenesis in humans remains to be an unresolved problem. Until now, the bacteria and viruses which have been accepted as participating in oncogenesis, include Helicobacter pylori, Chlamydia trachomatis, Chlamydia pneumoniae , as well as viruses of four families, including Herpesviridae (EBV, HHV8), Papillomaviridae (HPV), Retroviridae (HTLV) and Hepadnaviridae (HBV) . The respective role of filamentous fungi has also been accepted, notably including effects of Aspergillus and Fusarium , which produce cancer- -inducing mycotoxins. Alfatoxins, fumonisins, ochratoxins, zearalenone are amongst numerous fungal metabolites that have been linked with cancers of breast, liver, oesophagus and prostate. In turn, a chronic inflammatory reaction and an anti-apoptotic effect induced by Helicobcter pylori and bacteria of Chlamydia genus may be etiopathogenetically linked to, respectively, gastric cancer, tumours of uterine cervix or of lungs. Oncogenic properties of some viral proteins have been well documented. In EBV infection – induced carcinogenesis the most significant roles are played by BHRF1, EBNA-2 and LMP-1 proteins. They inhibit apoptosis and, in parallel, induce NF-κB activation and de-repression of genes responsible for cell resistance to TNF-α-induced cytotoxicity. In the process of HPV-induced carcinogenesis, significant roles are played by small proteins, E6 and E7, which interact with key cell cycle–controlling molecules. This results in deregulation of the cell cycle and in uncontrolled proliferation. Oncogenic properties of HTLV are determined by the virally–coded proteins, Rex and Tax, the transforming activity of which is linked to altered expression of cellular genes. In turn, HBV carcinogenicity seems to be conditioned by the viral protein, pX, which inactivates p53 and exhibits a transactivating potential.